Bonding ability of paste-paste glass ionomer systems to tooth structure: in vitro studies - Cook, N. B.; Feitosa, S. A. [UNESP]; Patel, A.; Alfawaz, Y.; Eckert, G. J.; Bottino, M. C. (Operative Dentistry Inc, 2015)
This study investigated the effect of nonrinse conditioners (ie, Ketac Nano Primer [KNP] and GC Self Conditioner [SC]) used as substrate pretreatment and their respective paste-paste resin-modified glass-ionomer cement (RMGIC) (ie, Ketac Nano [KN] and Fuji Filling LC [FF]) on microtensile bond strength to dentin and marginal sealing when compared with traditional RMGIC (ie, Photac Fil [PF] and Fuji II LC [FII]) used in association with polyacrylic acid (ie, Ketac Cavity Conditioner [KC] and GC Cavity Conditioner [CC]). A total of 192 extracted human molars were allocated into eight groups: KNP-KN, KC-KN, KNP-PF, KC-PF, SC-FF, CC-FF, SC-FII, and CC-FII. For microtensile bond strength, the teeth were sectioned to expose occlusal dentin and restored according to the group. After 24 hours the teeth were cut to yield nine beams per tooth (+/- 0.8 mm(2)). Testing was done using a universal testing machine followed by failure mode classification. For microleakage testing, standardized cavity preparations were made on the buccal cementoenamel junction and restored according to the group. The teeth were thermocycled (500 cycles, 8 degrees C to 48 degrees C), sealed, immersed in methylene blue for 24 hours, and then assessed for microleakage using a stereomicroscope. Microtensile bond strengths in megapascals (mean +/- SE) were KNP-KN: 14.9 +/- 1.6, KC-KN: 17.2 +/- 1.5, KNP-PF: 31.2 +/- 1.6, KC-PF: 26.2 +/- 1.2, SC-FF: 23.6 +/- 1.5, SC-FII: 31.2 +/- 1.5, and CC-FII: 21.9 +/- 1.5. Cervical margins showed more microleakage compared with occlusal margins. Overall, the use of nonrinse conditioners in association with traditional RMGICs demonstrated superior microtensile bond strengths to dentin when compared with the paste-paste RMGICs. Meanwhile, the association between polyacrylic acid (CC) and a traditional RMGIC (FII) led to the least microleakage for cervical locations when compared with all other groups.